Human Resource Management In Improving The Economy And Supporting Community Education Through Msme Activities In Tanjung Luar Village - Abdurrahim; Saprudin Efendi; Abdul Kohar (Pendidikan Al-Gafari, 2023)
Source Power man is often called a human resource, energy or strength human (energy or power). Humans are also mentioned as a source of energy, ability, strength, and expertise possessed humans, are also possessed by creatures, such as animals, and plants, and even also owned by elements. Study This aims to know from support government to business group society and how impact business programs on the sector economy and education for the community Type of research used is study descriptive qualitative, data obtained from observation, interviews, and documentation. Validity of researcher data uses technique triangulation. Data analysis was carried out with four stages namely: data collection, data reduction, data presentation, and withdrawal conclusion. Research results show: that there is support government with methods to protect and facilitate form tool production and deliver training for development capacity member group Bujamatas, so impact on addition from facet sector economics and education for group.